Influence of hypoxic hypoxia on some hematological, cardiovascular and respiratory parameters of men residing in the Colca Valley (3417-3633 msnm.) - Edgard Quispe Alfaro (2019)
The influence of hypoxic hypoxia on some hematological, cardiovascular and respiratory parameters of men residing in the Colca Valley (3417-3633 masl) was evaluated. The experimental evaluation was carried out at the Chivay Health Center and Health Post of Yanque, during the months of January to December 2015. The average age was 22.76 ± 5.04 years, average weight is 58.94 ± 6.16 Kg, average height of 1.64 ± 5.02 mt (p> 0.05). There was no significant difference in age, weight, height and BMI in the residents of Chivay, Yanque and Achoma. Significant difference in erythrocyte count, hematocrit and hemoglobin was found in the inhabitants of Chivay, Yanque and Achoma (p <0.05). There was no significant difference in leukocyte count in the assessed population (p> 0.05). There was no significant difference in leukocyte count in the inhabitants of Chivay, Yanque and Achoma (p> 0.05). A significant difference was found in the MCV (p <0.01). No significant difference was found in the corpuscular parameters HCM, CHCM. In the Tukey post-comparison test a significant increase (p <0.05) was found in the VCM of the Chivay resident individuals. A significant difference was found in the pulse (p <0.05). No significant difference was found in the PS, PD, PP, PMF corpuscular parameters. In the Tukey post-comparison test a significant increase (p <0.05) was found in the pulse of Chivay resident individuals. No significant difference was found in the chest diameter and respiratory rate (p> 0.05).